------------------------------------------------------------------------------------------
Equation
------------------------------------------------------------------------------------------
y = -3x - 9
------------------------------------------------------------------------------------------
Option 1
------------------------------------------------------------------------------------------
If I substitute x = -9, I should get y = 0
When x = -9
y = -3 (-9) - 9
= 18 (I did not get 0, wrong)
------------------------------------------------------------------------------------------
Option 2
------------------------------------------------------------------------------------------
If I substitute x = -3, I should get y = 0
y = -3(-3) - 9
y = 9 - 9
y = 0 (Yes, I got 0, correct)
------------------------------------------------------------------------------------------
Option 3
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -3
y = -3 (0) - 9
y = 0 - 9
y = -9 (I did not get -3, wrong)
------------------------------------------------------------------------------------------
Option 4
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -9
y = -3 (0) - 9
y = 0 - 9
y = -9 (Yes, I got -9, correct)
------------------------------------------------------------------------------------------
Answer: (-3, 0) and (0, 9) are ordered pairs of the equation (Answer B, D)
------------------------------------------------------------------------------------------
Answer:
22.5 weeks
Step-by-step explanation:
y = 1.12x + 28.78 represents the height of the puppy. Here that height is 54 cm:
Then 54 = y = 1.12x + 28.78
Combining the constants, we get 1.12x = 25.22. Dividing both sides by 1.12, x turns out to be 22.5 weeks.
Answer:
Step-by-step explanation:
2(6x² - 3) = 11x² - x
2*6x² - 2*3 = 11x² - x
12x² - 6 = 11x² -x
Subtract 11x² from both sides
12x² - 11x² - 6 = -x
x² - 6 = -x
x² + x - 6= 0
Sum =1
Product = -6
Factors = 3 , (-2) { 3*(-2) = -6 & 3 +(-2) = 1}
x² + 3x - 2x - 6 = 0
x(x + 3) - 2(x + 3)= 0
(x +3)(x - 2) = 0
Break it down into 2-Dimensional shapes. Then add the areas together.
From the picture you can see;
front & back rectangles are 2*(4 x 8) = 64 m²
2 side rectangles are 2*(4 x 12) = 56 m²
2 triangular front & back pieces are (1/2)*8*3 = 12 m²
2 roof rectangles are 2*(5 x 12) = 120 m²
total Surface area = 64 m² + 56 m² + 12 m² + 120 m²
= 252 m²
For the volume; break it up into 3-dimenssional shapes and add the volumes together.
From the picture you can see;
Rectangular box volume is 4 x 8 x 12 = 384 m³
Triangular roof volume is area of front triangle multiplied through the length. (1/2)*8*3* 12 = 144 m³
Total volume = 384 m³ + 144 m³
= 528 m³
Gradient:3
Y intercept:(0,2)